From risk to resilience: Ownership moderation in the geopolitical risk–cash holdings nexus of Indonesian banks - NAFIS DWI KARTIKO (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2026)
Purpose — This study examines the effect of geopolitical risk on bank cash holdings in Indonesia and investigates whether institutional, foreign, and government ownership moderate this relationship. Method — The empirical analysis employs System Generalized Method of Moments (System GMM) to address endogeneity inherent in dynamic panel models with lagged dependent variables. Serial correlation is diagnosed via the Arellano–Bond test, and instrument validity is confirmed through Hansen and Sargan tests. Findings — Geopolitical risk, including both perceived threats and realized geopolitical events, has a significant negative effect on bank cash holdings. The results also indicate persistence in banks’ cash policies. Institutional ownership positively affects cash reserves; however, its interaction with geopolitical risk is negative, suggesting that geopolitical pressures weaken the prudential role of institutional investors. Foreign and government ownership shows no significant direct or moderate effects. Implications — Bank managers and regulators should incorporate geopolitical exposure and ownership characteristics into liquidity risk assessment and cash management policies. Adaptive liquidity frameworks are necessary to balance financial resilience and intermediation efficiency during periods of heightened global uncertainty. Originality — This study provides new evidence on the joint influence of external geopolitical shocks and internal ownership structures on bank liquidity decisions in an emerging economy.